INNOVATIVE APPROACHES TO TOURISM RISK MANAGEMENT: INCREASING RESILIENCE AND ADAPTATION TO CRISIS - Marbawi; Nurfaliza; Aiyub Yahya (PT. Radja Intercontinental Publishing, 2025)
The tourism industry is increasingly vulnerable to various crises, such as natural disasters, political instability, and health emergencies. Traditional risk management approaches often focus on reactive measures and short-term solutions, failing to address the root causes of vulnerability and build long-term resilience. This study explores the limitations of traditional tourism risk management practices and investigates the potential of innovative strategies to enhance the resilience and adaptability of the tourism sector in the face of crises. Through a comprehensive literature review, the study identifies key characteristics of innovative risk management approaches, including proactive planning, systems thinking, adaptive management, and multi-stakeholder collaboration. The findings highlight the importance of effective governance structures, strong leadership, and a culture of learning and knowledge sharing in the successful implementation of these strategies. The study also reveals the critical role of technology and digital tools in enhancing resilience and adaptability, as well as the potential of community-based approaches to risk management. However, the research acknowledges the need for further investigation into the factors that enable or hinder the adoption of innovative practices in different tourism contexts, as well as the specific challenges posed by different types of crises. The study concludes by emphasizing the importance of a holistic and proactive approach to tourism risk management, engaging diverse stakeholders, and fostering a culture of resilience and adaptability. The findings provide valuable insights for tourism practitioners, policymakers, and researchers seeking to develop more effective and sustainable risk management strategies in the face of an increasingly complex and uncertain global environment.